Lipoteichoic acid from Lactobacillus rhamnosus GG as an oral photoprotective agent against ultraviolet-induced carcinogenesis - Weill, Federico S. (2013)
Probiotics are live micro-organisms that when administered in adequate amounts confer a health benefit on the host. Cell surface molecules of these micro-organisms are being studied in relation to their ability to interact with the host. The cell wall of lactobacilli possesses lipoteichoic acids (LTA) which are molecules with immunomodulatory properties. UV radiation (UVR) has been proposed as the main cause of skin cancer because of its mutagenic and immunosuppressive effects. Photoprotection with some nutrition interventions including probiotics has recently been shown. The aim of the present study was to investigate whether the oral administration of purified LTA from Lactobacillus rhamnosus GG can modulate the immune-suppressive effect of UVR and skin tumour development in female Crl:SKH-1-hrBR mice. For this purpose, two irradiation models were studied: (1) a chronic irradiation scheme consisting of daily irradiations during twenty consecutive days and (2) a long-term irradiation schedule, irradiating the animals three times per week, during 34 weeks for tumour development. The results showed that T-cells in the inguinal lymph node of LTA-treated mice produced higher levels of (1) interferon-γ and (2) a number of total, helper and cytotoxic T-cells compared with non-treated mice. Moreover, a significant delay in tumour appearance was found in LTA-treated mice. An increased IgA+ cell number was found in the small intestine together with a higher number of activated dendritic cells in the mesenteric lymph nodes. The latter results might be indicative of a direct effect of LTA in the gut, affecting the cutaneous immune system and restoring homeostasis through the gut–skin axis.